Arctic science and politics in Fascist Italy. Italian polar expeditions and the International Polar Exhibition in the interwar years. (2nd January 2023) - Ferrarini, Fabio
ABSTRACT: In 1928, the airship Italia, commanded by Umberto Nobile, crashed on the way back from the North Pole. The tragic outcome of his expedition interrupted the organization of significant Arctic explorations and generated a fracture between Mussolini's regime and polar studies. The Fascist regime implicitly expressed its shame for its role in the whole unfortunate expedition and the subject became taboo in the entire country. Almost ten years later, in 1937, Norway invited all countries that had previously undertaken polar expeditions to participate in the first International Polar Exhibition ( Internasjonal utstilling for polarforskning ), planned to be held from May 1940. Considering the polemics after the 1928 Arctic expedition, the Norwegians' eager efforts to solicit Italy's participation in the exhibition may appear surprizing. Therefore, this work aims to better understand these dynamics, seeing the uncertainties surrounding Italy's participation in the polar exhibition in light of Nobile's pivotal role in the organization of Fascist Italy's polar explorations.